Maternal satisfaction among mothers delivering at public health facilities in India: a narrative review - Vyas, Himanshu; J., Mariam O.; Bhardwaj, Pankaj (International Journal Of Community Medicine And Public Health, 2022)
Satisfaction is considered as a very important indicator of quality of services. Availability of patient centered services ensures optimum utilization and compliance to interventions. Maternal satisfaction with the available childbirth services has an impact on her birthing experience and ability to bond with the newborn. Multiple factors influence maternal satisfaction with childbirth services. This narrative review summates the level of maternal satisfaction with child birth services at public health facilities and its determinants. PubMed and Google Scholar data base were searched using various keywords and Mesh terminologies. Reference lists of related articles were also screened. This review concluded that the majority of the mothers were satisfied with the child birth services available at the public health facilities. All three domains of the Donabedian model of quality care including the structure, process and outcome were among the determinants of maternal satisfaction but process of care dominated the determinants of maternal satisfaction. Interpersonal behavior was a key determinant of maternal satisfaction; other determinants were provision of privacy, availability and perceived competency of human resource and cleanliness of the labor room.